Construction material assessment from quarry sites at Chaktan-Ghasa-Kaligandaki River area, western Nepal (Bulletin of the Department of Geology, 2011)
Construction material assessment is the crucial part of the hydroelectric power projects. The quality and quantity of the construction materialis the major concern when exploring construction material. Four quarry sites (Q1, Q2, Q3 and Q4) were identified and assessed for both quantityand quality. Distribution of rock quarry sites was taken for quantitative assessment of reserves. The rock samples were obtained from the sitesand were analysed for physical, mechanical and petrographic features. Rock types in quarry sites were schistose marble (in Q1), augen gneiss(in Q2), and banded gneisses (in Q3 and Q4). The analytical results showed that water absorption values were < 1% in all the samples, but wasthe highest in Q2 (0.92%). Contrarily, Q2 possessed the least specific gravity among the samples. Sodium sulphate soundness values rangedfrom 0.21 to 0.77, which was the highest in Q2. Samples Q1, Q3 and Q4 yielded Los Angeles Abrasion value below 45%, whereas Q2 gave57.5%. Similarly, Q2 also yielded the least value (1.82 MPa) of point-load strength index tested along the foliation. Augen gneiss (Q2) showedthe low abrasion resistance and soundness to freeze and thaw because of weak bonding between platy and other constituents of the rock , whereasschistose marble and banded gneisses yielded better resistance to abrasion and freeze and thaw, and possessed better strength perhaps due towell bonding among the mineralogical constituents due to the presence of appreciable amount of carbonate minerals.DOI: http://dx.doi.org/10.3126/bdg.v14i0.5442Bulletin of the Department of Geology Vol.14 2011, pp.77-82